2020
DOI: 10.1002/phar.2459
|View full text |Cite
|
Sign up to set email alerts
|

Treprostinil Attains Clinically Therapeutic Concentrations in Neonates with Pulmonary Hypertension on Extracorporeal Membrane Oxygenation Support

Abstract: Background: Treprostinil is a prostacyclin analog used for treatment of pulmonary hypertension (PH) in adults and children, currently awaiting clinical assessment for use in neonates.Objectives: We aimed to investigate the use of treprostinil in neonates with PH on extracorporeal membrane oxygenation (ECMO) support and measure plasma concentrations of the drug.Methods: This is a retrospective case‐series with prospectively collected blood samples, conducted in a quaternary care neonatal intensive care unit.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Overall, 12 clinical trials on treprostinil for children with PH were registered on the clinical trial registries from the World Health Organization network (16). According to previous reports, TRE therapy is safe and efficacious in pediatric CHD patients with PAH (17)(18)(19). Intravenous (IV) or subcutaneous (SC) administration are two available options for continuous TRE use (13).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Overall, 12 clinical trials on treprostinil for children with PH were registered on the clinical trial registries from the World Health Organization network (16). According to previous reports, TRE therapy is safe and efficacious in pediatric CHD patients with PAH (17)(18)(19). Intravenous (IV) or subcutaneous (SC) administration are two available options for continuous TRE use (13).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the therapeutic effect of TRE in pediatric patients with PAH, but documented results of TRE in pediatric patients with FSV-PAH are lacking. The goal dose of TRE was approximately 20 ng/kg/min in many studies (18,21). De Bie et al reported TRE concentrations during clinical treatment in four neonates on extracorporeal membrane oxygenation support (18).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations